2004
DOI: 10.1038/sj.bjc.6602003
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer among users of aspirin and other anti-inflammatory drugs

Abstract: We conducted a cohort study with a nested case -control analysis to evaluate the effect of anti-inflammatory drugs in breast cancer incidence using the General Practice Research Database. Women taking aspirin and paracetamol for 1 year or longer had an odds ratio (OR) of 0.77 (95 percent confidence interval (95% CI): 0.62,0.95) and 0.76 (95% CI: 0.65,0.88), respectively, compared to nonusers. Daily doses of aspirin (75 mg) and paracetamol (up to 2000 mg) showed the greatest reduced risk. Use of non-aspirin non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…In our study, paracetamol was protective for bladder cancer among individuals who were GSTP1 I105V wild-type homozygous and was nonsignificantly associated to an increased risk of bladder cancer among subjects homozygous for GSTP1 minor allele. If these findings are replicated, they may suggest that GSTP1 is responsible for the inactivation of the toxic metabolite (NAPQI) of paracetamol and that the inability to eliminate this DNA adduct-forming compound may override the chemoprotective properties of paracetamol described elsewhere for bladder cancer (9,11) and breast cancer (54).…”
Section: Cancer Epidemiology Biomarkers and Prevention 1699mentioning
confidence: 99%
“…In our study, paracetamol was protective for bladder cancer among individuals who were GSTP1 I105V wild-type homozygous and was nonsignificantly associated to an increased risk of bladder cancer among subjects homozygous for GSTP1 minor allele. If these findings are replicated, they may suggest that GSTP1 is responsible for the inactivation of the toxic metabolite (NAPQI) of paracetamol and that the inability to eliminate this DNA adduct-forming compound may override the chemoprotective properties of paracetamol described elsewhere for bladder cancer (9,11) and breast cancer (54).…”
Section: Cancer Epidemiology Biomarkers and Prevention 1699mentioning
confidence: 99%
“…In this casecontrol study, the lower dose was more effective (the relative risk decreased 33%) in comparison to the higher doses, where no significant differences were obtained (aspirin RR=0.77; NSAIDs (non-aspirin) RR=1.00; acetaminophen RR=0.76). Moreover, they reported that there was no correlation between time of intake and benefit (32).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…In the effort to determine an optimal dose administration of aspirin, García-Rodríguez et al studied 3,708 patients who were divided into three experimental groups according to aspirin concentration: 75, 150 or 300 mg (32). In this casecontrol study, the lower dose was more effective (the relative risk decreased 33%) in comparison to the higher doses, where no significant differences were obtained (aspirin RR=0.77; NSAIDs (non-aspirin) RR=1.00; acetaminophen RR=0.76).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…Results from epidemiological studies of breast cancer, however, are conflicting [9], despite many meta-analyses having indicated a chemopreventive effect of aspirin or NSAIDs against the disease [8,10,11,12,13]. In contrast, some cohort and case-control studies have reported no reduced risk of breast cancer from use of either aspirin [14,15,16,17,18,19,20,21,22] or non-aspirin NSAIDs [14,15,16,17,23,24]. …”
Section: Introductionmentioning
confidence: 99%